Potensi Produk Kombucha pada UMKM Ximbucha Bandung Jawa Barat - Rahmi, Sakinah Aini; Ernah, Ernah; Mulyana, Asep (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
In recent years, the trend of consuming natural-based health products has increased, encouraging the exploration of butterfly pea flowers as a raw material for functional beverage products such as kombucha. Butterfly pea flower kombucha is an innovative alternative that combines the benefits of fermentation with the richness of bioactive compounds from butterfly pea flowers. This study aims to assess the potential of kombucha products made from butterfly pea flowers (Clitoria ternatea L.) through a case study of the Ximbucha MSME in Bandung and Tasikmalaya. The methods used in this study are Supply Chain Operations Reference (SCOR) for supply chain process mapping, Analytic Hierarchy Process (AHP) for strategic prioritization, and SWOT analysis. The results show that the potential of kombucha products is evident in the development of a supply chain that relies on upstream-downstream actor collaboration, operational efficiency, and the use of data-driven technology. Recommended strategies include strengthening partnerships with butterfly pea flower farmers, optimizing logistics, and utilizing digitalization in promotions and customer management.